PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL INTERAKTIF PADA MATERI POKOK BILANGAN KELAS VII SMP/MTs - Sonya Claudy Emellya Putri; Sehatta Saragih; Nahor Murani Hutapea (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is a developmental research which aims to produce computer based learning media of an interactive tutorial model in main value topic for 7th grade of SMP/MTs that is valid and practical. This developmental research used development model based on the teory of Borg and Gall modified by Sugiono (2011). The stages are: (1) potential and problem; (2) literature collection; (3) product design; (4) product validation; (5) product revision; (6) product tested; (7) product revision; (8) product tested in large group; (9) product revision. Product design is through two stages, that are making paper based design and then used microsoft office power point program. The research instrument used a validation sheet that was validated by three experts or validators and participant response questionnaires assessed by students. Assessment of validation data and questionnaire responses of students is done by adapting the formula from Anas Sudijono (2011). The results of the validation of three experts or validators obtained an average score of 3.31 (very valid). The product testing on 6 students of class VII SMP PGRI Pelalawan with an average score of 3.83 (very practical). Furthermore, a trial of use or trial of a large group on 22 students of class VII SMP PGRI Pelalawan with an average score of 3.46 (very practical). Thus, it can be concluded that computer based learning media is valid and practical.Key Words : Computer based Interactive Learning Media, Development, Main Value